(untitled) (Global Journals of Research in Engineering, 2012)
The textile industry is one of the oldest and largest sector in India. It generates liquid waste from its different processes. After treatment of the textile waste water in Effluent Treatment Plants, sludge is generated. Government has allotted specific location for its disposal. Generated sludge mostly disposed in landfill and dumping in the specified areas by Government. The transportation and disposal process is very costly. In this study an attempt is made to find out the feasibility of using sludge textile mill sludge as fine aggregates in M:20 grade of concrete. The replacement of fine aggregate with sludge in conventional concrete mix affects workability and density of concrete. The compressive strength gradually reduces with replacement and later it falls below desired value when fine aggregate replaced by textile mill sludge is beyond 32%. The fly ash is added to replace cement along with 32% sludge. It shows slight decrease in compressive strength. The fly ash i.e. byproduct from thermal power plants is now no more a waste. This is also clubbed with Textile Mill Sludge to use in concrete. The trials are also taken on concrete cubes with combination of Textile Mill Sludge and fly ash.